The intermediary bodies of technopolitics: from the logic of representative to the logic of representation - Giacomazzi, Marco (Rivista Italiana di Filosofia del Linguaggio, 2023)
On December 15, 2016, Mark Zuckerberg acknowledged that Facebook had surpassed his initial conception of a technology that information flows through" and was compelled to declare it as a new kind of platform for public discourse. The introduction of computer and digital systems into democratic life has transformed the dynamics of political discourse, representing a paradigm shift in the mediated participation in public life. Technopolitics, understood as the evolution of mechanisms for delegating sovereignty through technological systems of representation (like representative democracy), constitutes the field in which we examine the complexities of mediating political positions through digital media. The objective of this essay is to identify the semiotic mechanisms underlying participation in public discourse mediated by digital platforms. At the core of democracy lies a consensus-building mechanism that involves delegation of power to representatives: what happens when that consensus is constructed through digital platforms? What logics guide the construction of political discourse in these contexts?